2002
DOI: 10.1068/p3254
|View full text |Cite
|
Sign up to set email alerts
|

Blur Discrimination and its Relation to Blur-Mediated Depth Perception

Abstract: Abstract. Retinal images of three-dimensional scenes often contain regions that are spatially blurred by different amounts, owing to depth variation in the scene and depth-of-focus limitations in the eye. Variations in blur between regions in the retinal image therefore offer a cue to their relative physical depths. In the first experiment we investigated apparent depth ordering in images containing two regions of random texture separated by a vertical sinusoidal border. The texture was sharp on one side of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 10 publications
5
88
1
Order By: Relevance
“…The results showed that the increment threshold of blur first decreased and then increased with increasing levels of blur in the reference blur circle, resulting in a parabolic shape of the relationship between the threshold and the reference blur with a peak sensitivity around one arcmin. Consistency in these results was shown across a variety of studies in spite of different stimuli and experimental methods (Hess, Pointer, & Watt, 1989;Mather, 1997;Mather & Smith, 2002;Watt & Morgan, 1983;Wuerger, Owens, & Westland, 2001). Assuming a peak ability to discriminate blur at about one arcmin, we may predict that this value is the limiting factor in discriminating DOF.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…The results showed that the increment threshold of blur first decreased and then increased with increasing levels of blur in the reference blur circle, resulting in a parabolic shape of the relationship between the threshold and the reference blur with a peak sensitivity around one arcmin. Consistency in these results was shown across a variety of studies in spite of different stimuli and experimental methods (Hess, Pointer, & Watt, 1989;Mather, 1997;Mather & Smith, 2002;Watt & Morgan, 1983;Wuerger, Owens, & Westland, 2001). Assuming a peak ability to discriminate blur at about one arcmin, we may predict that this value is the limiting factor in discriminating DOF.…”
Section: Introductionmentioning
confidence: 86%
“…First, the definition of DOF in our paper was based on the blur circle of one arcmin. Second, the peak sensitivity for blur discrimination was found to be around one arcmin (Chen, Chen, Tseng, Kuo, & Wu, 2009;Hamerly & Dvorak, 1981;Hess, Pointer, Simmers, & Bex, 2003;Mather & Smith, 2002;Watt & Morgan, 1983).…”
Section: Predicting Jnds Of Dof From Blur Discriminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Mather et al [2002] showed that when only pictorial cues are considered, the blurred textures in Fig. 2 should appear as being behind the others.…”
Section: Introductionmentioning
confidence: 99%